Brushite ceramic coatings for dental brace brackets fabricated via aerosol deposition. Issue 1 (January 2017) - Lee, Dong-Won; Shin, Min-Chul; Kim, Yong-Nam; Oh, Jong-Min
Abstract: Biocompatible ceramic coatings were fabricated at room temperature by via aerosol deposition (AD), in order to improve the bonding strength between the dental sapphire bracket and the resin. First, the deposition properties of the brushite films coated on the flat sapphire substrate were investigated, confirming their good deposition rate and appropriate adhesive strength. Then, the mesh and check patterns of the coatings were formed on the sapphire brackets in order to obtain a sufficient shear bond strength. The mesh-pattern grown by converging nozzles exhibited a low film thickness (<10 µm) and shear bond strength (<7 MPa) due to the sharp triangular-shaped cross sections. In contrast, the check-pattern showed a high film thickness of 70 µm at the same deposition time, as well as a high shear bond strength of 14 MPa, implying that this check-pattern brushite coating formed via the AD process is a promising candidate for application in dental brace brackets.